Radiotherapy of the Hepatocellular Carcinoma in Mice Has a Time-Of-Day-Dependent Impact on the Mouse Hippocampus - Mona Yassine; Soha A. Hassan; Simon Sommer; Lea Aylin Yücel; Hanna Bellert; Johanna Hallenberger; Dennis Sohn; Horst-Werner Korf; Charlotte von Gall; Amira A. H. Ali (Cells, 2022)
Chronic liver diseases including hepatocellular carcinoma (HCC) create a state of chronic inflammation that affects the brain via the liver–brain axis leading to an alteration of neurotransmission and cognition. However, little is known about the effects of HCC on the hippocampus, the key brain region for learning and memory. Moreover, radiotherapy used to treat HCC has severe side effects that impair patients’ life quality. Thus, designing optimal strategies, such as chronotherapy, to enhance the efficacy and reduce the side effects of HCC treatment is critically important. We addressed the effects of HCC and the timed administration of radiotherapy in mice on the expression of pro-inflammatory cytokines, clock genes, markers for glial activation, oxidative stress, neuronal activity and proliferation in the hippocampal neurogenic niche. Our data showed that HCC induced the upregulation of genes encoding for pro-inflammatory cytokines, altered clock gene expressions and reduced proliferation in the hippocampus. Radiotherapy, in particular when applied during the light/inactive phase enhanced all these effects in addition to glial activation, increased oxidative stress, decreased neuronal activity and increased levels of phospho(p)-ERK. Our results suggested an interaction of the circadian molecular clockwork and the brain’s innate immune system as key players in liver–brain crosstalk in HCC and that radiotherapy when applied during the light/inactive phase induced the most profound alterations in the hippocampus.